Neonatal hyperekplexia with homozygous p.R392H mutation in GLRA1. Issue 3 (September 2014) - Hmami, Fouzia; Wood, Sian‐Elin; Chaouki, Sana; Oulmaati, Abdellah; Hida, Mustapha; Rees, Mark I.; Chung, Seo‐Kyung; Bouharrou, Abdelhak
<x xml:space="preserve">Abstract</x> Hyperekplexia is a rare neurogenetic disorder, frequently misdiagnosed in neonates with a risk of apnoea, asphyxia, and sudden infant death. We present video sequences of a male newborn, admitted on the second day of life to the neonatal intensive care unit, due to tonic‐clonic movements. Following clinical and paraclinical investigations, a final diagnosis of hyperekplexia was made. Genetic analysis revealed a homozygous mutation in GLRA1 resulting in a R392H amino acid substitution and altered receptor dynamics, as indicated from previous work. The infant showed a marked improvement of the startle response and muscle hypertonia with clonazepam which is a strong clinical feature of GLRA1‐mediated hyperekplexia. [Published with video sequences]